Comprehensive spinal correction rehabilitation (CSCR) study: a randomised controlled trial to investigate the effectiveness of CSCR in children with early-onset idiopathic scoliosis on spinal deformity, somatic appearance, functional status and quality of life in Shanghai, China - Tongtong Zhang; Xin Li; Xuan Zhou; Qing Du; Yingxian Li; Qimeng Fan; Juping Liang; Zhengquan Chen; Haibin Guo; Lili Cai (BMJ Open)
Introduction Presently, the physiotherapy scoliosis-specific exercise recommended by the International Scientific Society on Scoliosis Orthopaedic and Rehabilitation Treatment guidelines is primarily advised for adolescents with scoliosis, and there is a lack of individualised and precise exercise therapy for children with early-onset idiopathic scoliosis (EOIS), whose bodies are in the nascent stages of development. Therefore, this study aims to investigate the efficacy of comprehensive spinal correction rehabilitation in treating EOIS.Methods and analysis This study will be designed as a randomised controlled trial, and the subjects participating in the study will consist of 122 EOIS patients between the ages of 7–10 years. Subjects will be randomly assigned to an experimental group (n=61) and a control group (n=61). Both groups will be treated for 6 months, with the experimental group receiving comprehensive spinal correction rehabilitation (including specific exercise therapy, balance and stability training, breathing training, strength training, home-based exercise and bracing) and the control group receiving core stability training. Enrolled subjects will be evaluated at the initial visit and after 6 months of treatment, and data will be processed and analysed after collecting data from both evaluations. The primary outcome index is the major curvature Cobb angle, and the secondary outcome indices are the angle of trunk rotation, plumb line distance, the Trunk Aesthetic Clinical Evaluation index, forced vital capacity and the Scoliosis Research Society-22 questionnaire.Ethics and dissemination The current study received ethical approval from the Xinhua Hospital Ethics Committee Affiliated to Shanghai Jiao Tong University School of Medicine (XHEC-C-2023-108-3). Written informed consent will be obtained from all participants and their guardians. Any interim analyses and full results will be published in an international peer-reviewed journal.Trial registration number The study protocol was registered at www. Clinical trials. gov (number identifier: ChiCTR2300078359).